Correlation Between Postpartume Literacy and Depression Among Women - Sholihat, Siti; Paduragan, Santhna Lechmi; Nambiar, Nisha; Zani , Benny Novico (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims : Mental health literacy involves understanding and coping with mental health issues, accessing information, and maintaining a healthy mindset. However, the average public struggles with mental health and postnatal depression. Researchers aim to investigate the impact of postpartum depression education on the depression rate among new mothers in Indonesia. Methods : This study, conducted in Depok, Indonesia, aimed to assess postpartum depression knowledge among women with single deliveries, postpartum days 10-3 months, and normal babies, using the PoDLiS test and Beck Depression Inventory II. Results : The Pearson correlation coefficient was utilized to examine the relationship between postpartum literacy and postpartum depression in women. This study included about 310 women. The average age was 31.56 years (with a standard deviation of 5.37 years). Postpartum literacy was found to be linked with postpartum depression (r=0.453, p0.05). Conclusions : Postpartum depression was linked to postpartum literacy. All women attending postnatal clinics should be subjected to simple screening measures early in the postpartum period, and this should continue for at least a year or two after birth.